2015
DOI: 10.1371/journal.pone.0116594
|View full text |Cite
|
Sign up to set email alerts
|

A New Mouse Model of Mild Ornithine Transcarbamylase Deficiency (spf-j) Displays Cerebral Amino Acid Perturbations at Baseline and upon Systemic Immune Activation

Abstract: Ornithine transcarbamylase deficiency (OTCD, OMIM# 311250) is an inherited X-linked urea cycle disorder that is characterized by hyperammonemia and orotic aciduria. In this report, we describe a new animal model of OTCD caused by a spontaneous mutation in the mouse Otc gene (c.240T>A, p.K80N). This transversion in exon 3 of ornithine transcarbamylase leads to normal levels of mRNA with low levels of mature protein and is homologous to a mutation that has also been described in a single patient affected with la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“… 1 Plasma samples were extracted and analyzed for measuring the amino acid and formate concentrations ( n = 8–12/group). These results are within mice’s normal range compared to the literature [ 22 ]. 2 Plasma formate enrichments in mice received L-[2,3,3- 2 H 3 ]-Serine or [2- 13 C]-Glycine tracers ( n = 2–3/group).…”
Section: Figuresupporting
confidence: 84%
“… 1 Plasma samples were extracted and analyzed for measuring the amino acid and formate concentrations ( n = 8–12/group). These results are within mice’s normal range compared to the literature [ 22 ]. 2 Plasma formate enrichments in mice received L-[2,3,3- 2 H 3 ]-Serine or [2- 13 C]-Glycine tracers ( n = 2–3/group).…”
Section: Figuresupporting
confidence: 84%
“…10 Recently, Tarasenko described the spf-j mouse affected by a spontaneous mutation in the Otc gene (c.240T>A, p.Lys80Asn), in which the transversion in exon 3 results in normal levels of mRNA with low levels of mature protein. 11 This variation was described in one OTCD patient with late onset. 12 The hypomorphic spf-j mouse displays a very mild phenotype with residual enzyme activity of 10% to 12% and has normal plasma ammonia and orotic acid excretion.…”
Section: Introductionmentioning
confidence: 84%
“…12 The hypomorphic spf-j mouse displays a very mild phenotype with residual enzyme activity of 10% to 12% and has normal plasma ammonia and orotic acid excretion. 11 Another model, which in fact has been widely used, is the spf ash (abnormal skin and hair) mouse. This mouse carries a point mutation that is also found in human patients, Otc c.386G>A, and that affects the last nucleotide of exon 4, which leads to a benign missense change p.Arg129His and to an abnormal splicing of exon 4.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have demonstrated that HHs isolated from patients with genetic metabolic diseases, including OTCD and other UCDs, proliferate in humanized liver mouse models. 15,16,23,24 Furthermore, some have a disease phenotype, such as carbamoyl phosphate synthetase-1 (CPS-1) deficiency 24 and familial hypercholesterolemia, 21 but not OTCD. In these studies, another representative humanized liver mouse model, FRG mice, with a genetic background of fumarylacetoacetate hydrolase (FAH) deficiency and immunodeficiency (Rag2 −/− IL2rg −/− ) were used.…”
Section: Discussionmentioning
confidence: 99%
“…OTC enzyme activity was determined by a colorimetric method based on the production of L-citrulline as described previously. 20,21 Citrulline production was determined by measuring the absorbance at 490 nm using a SpectraMax i3 Multimode microplate platform (Molecular Devices). The enzyme activity was expressed as citrulline μmol/mg protein/h.…”
Section: Otc Enzyme Activitymentioning
confidence: 99%